Attack on Titan : before the fall. 14 - Isayama, Hajime, 1986-; Suzukaze, Ryo (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2018)
An ultimatum has been issued: for the Survey Corps to continue the good fight of helping humanity expand beyond the Walls again, they must mount an expedition and prove that the new Vertical Maneuvering Equipment is capable of killing a Titan. But part of the preparation is to actually see the Titans and understand what humanity's greatest foe really looks like--a challenge more daunting than any written test...